Kemampuan Keuangan Daerah Pada Otonomi Daerah (Kajian dalam Manajemen Publik) - Yummil Hasan (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2013)
District and City government readiness in facing regional autonomy, particularly in the financial area, and to see the financial capacity of the area, which in this case is closely related to the reception area. Basically it can be said that there are differences in fiscal capacity between the District and the City, this difference visible due to the presence of urban amenities and the town's economy that is more complete, and the city has a better economic potential of the district. Thus, the role of PAD to the total budget cannot support the independence or the financial ability of the regional government in the era of autonomy in the District and the City entirely. However, comparison of the level of fiscal capacity in the analysis of the total budget revenue ratio between the District and the City, it can be said is which city has the better skill level of the district.